Using the Internet to Recruit Respondents for Offline Interviews in Criminological Studies. Issue 6 (November 2019) - Gundur, R.V.
Current and ex-gang members are hard-to-reach populations for research purposes. To date, researchers have resorted to embedding themselves long-term or recruiting individuals of interest within a target community. Typically, such studies provide a great deal of empirical depth but not necessarily empirical breadth given their lack of comparative analysis and generalizability. Moreover, they often rely on snowballing or chain referral methods that depend on the networks of the recruited seeds. This article explores the use of the Internet to recruit such individuals for face-to-face interviews. This strategy has been employed in settings outside criminology to good effect. This article shows that the online recruitment of current and ex-gang members not only reduces the time necessary to develop contacts but also allows researchers to triangulate data by encountering a diverse array of respondents.